To solve the equation step by step, let's start with the given information.
-
We have the equation:
\( 2(b + 12) = -6 \)
-
To isolate \( b + 12 \), we first divide both sides by 2:
\[ b + 12 = \frac{-6}{2} \]
Simplifying the fraction gives:
\[ b + 12 = -3 \]
-
Now, we want to isolate \( b \) by subtracting 12 from both sides:
\[ b = -3 - 12 \]
Combining the terms gives:
\[ b = -15 \]
Missing Terms and Descriptions:
-
First Missing Term: The equation \( 2(b + 12) = -6 \) simplifies to \( b + 12 = -3 \) after dividing both sides by 2.
- So the first missing term is: -3.
-
Missing Description: When we moved from \( 2(b + 12) = -6 \) to \( b + 12 = -3 \), we divided both sides by 2.
-
Finally, after simplifying, we found that:
- Then Combine to get: \( b = -15 \).
So the complete solution can be summarized as follows:
-
Equation: \( 2(b + 12) = -6 \)
-
Division step: \( b + 12 = -3 \)
-
Final step: \( b = -15 \)
-
Missing Terms:
- \( -3 \) (from \( b + 12 = -3 \))
- Division step description: Divide both sides by 2.
-
Final Answer: \( b = -15 \) after subtracting 12.